2017
DOI: 10.3892/mco.2017.1506
|View full text |Cite
|
Sign up to set email alerts
|

ATP‑binding cassette transporter A1: A promising therapy target for prostate cancer (Review)

Abstract: Abstract. ATP-binding cassette transporter A1 (ABCA1) has been found to mediate the transfer of cellular cholesterol across the plasma membrane to apolipoprotein A-I (apoA-I), and is essential for the synthesis of high-density lipoprotein.Mutations of the ABCA1 gene may induce Tangier disease and familial hypoalphalipoproteinemia; they may also lead to loss of cellular cholesterol homeostasis in prostate cancer, and increased intracellular cholesterol levels are frequently found in prostate cancer cells. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Sadly, other interesting ABCs, e.g., antigen processing ABCB2/ABCB3 or the translation regulating ABCE1, belong to the less studied molecules, similar to the physiologically important ABCs from A, D, and G subfamilies ( Table 1 ). The role of physiological substrates and active ABCs in cancer is being increasingly studied [ 170 , 171 , 172 ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Sadly, other interesting ABCs, e.g., antigen processing ABCB2/ABCB3 or the translation regulating ABCE1, belong to the less studied molecules, similar to the physiologically important ABCs from A, D, and G subfamilies ( Table 1 ). The role of physiological substrates and active ABCs in cancer is being increasingly studied [ 170 , 171 , 172 ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…For example, it has been reported that metabolic syndrome (MetS) is an obvious pathogenic factor for epithelial ovarian cancer [ 17 ]. The loss of cellular cholesterol homeostasis has been found frequently in prostate cancer cells [ 18 ]. Additionally, obesity has been confirmed to support the development and progression of melanoma and controlling body weight is effective for suppressing melanoma [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These are membrane-associated proteins that transport various molecules across extra- and intra-cellular membranes, and can expel drugs from the interior of the cell [101]. Indeed, increased ABCA1 expression has been previously observed to play a role in therapeutic resistance in other types of cancers [102, 103]. Thus, among other changes, the significant increase in ABCA1 expression observed in molm-13 R2 cells is consistent with the slow drug uptake predicted by the mathematical model.…”
Section: Resultsmentioning
confidence: 99%